Some problems of custody and guardianship establishment over minors in the Republic of Kazakhstan - Akimzhanova, M.T.; Tilep, T.S. (Bulletin of the Karaganda University “Law Series”, 2023)
The problem of the organization of minors deprived of parental care historically attracted the attention of states and society. In recent years, this question has gained special relevance. In “Strategy Kazakhstan–2050: a new political course of the established state”, first President of Kazakhstan, N. Nazarbayev emphasized that the protection of the rights of women and children is an important part of the new social policy. On the basis of the analysis of the current family–marriage, civil legislation of the Republic of Kazakhstan and law enforcement practice, topical issues of ensuring the rights and interests of minors under custody and guardian- ship are considered. The authors have noted that custody or guardianship are among the traditional institutions of ensuring guaranteed by the state constitutional rights, since the fate of a minor citizen in need of social patronage is determined by the most favorable way, on the one hand, close to family living, on the other one — there is a great positive potential, providing control over compliance with its legal rights and interests. The theoretical foundations and aspects of law enforcement provisions on the establishment, functioning and termination of custody and guardianship over minors is in the focus of a local point. By providing the results of their own theoretical research and in order to expand legal preconditions of the definition of custody and guardianship and to ensure the interests of orphaned children and children deprived of parental care the authors offer proposals that are aimed for improving the current domestic legislation in the designated sphere.